Efektivitas Pengisian Jabatan Fungsional dalam Meningkatkan Kinerja Pelayanan Publik pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sikka - Imanuel Wellem; Maria Modesta Missi Mone; Fredericko Lino Pereira (Jurnal Projemen UNIPA, 2025)
The Department of Population and Civil Registration of Sikka Regency is one of the public administration service providers in the East Nusa Tenggara region. This study aims to determine the effectiveness of functional position assignments in improving public service performance at the Department of Population and Civil Registration of Sikka Regency. The equalization of administrative positions into functional positions provides opportunities to clarify the roles and responsibilities of each employee in delivering services. This research employs a descriptive qualitative method, describing how effective the assignment of functional positions is in enhancing public service performance at the Department of Population and Civil Registration of Sikka Regency. The assignment of functional positions at the Department of Population and Civil Registration (Disdukcapil) of Sikka Regency has proven effective in improving public service performance. Functional positions oriented towards specific competencies and expertise strengthen the management of population and civil registration data accurately, systematically, and professionally.